2019
DOI: 10.1101/2019.12.24.888065
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A perinuclear microtubule-organizing center controls nuclear positioning and basement membrane secretion

Abstract: Non-centrosomal microtubule-organizing centers (ncMTOCs) have a variety of roles presumed to serve the diverse functions of the range of cell types in which they are found. ncMTOCs are diverse in their composition, subcellular localization, and function. Here we report a novel perinuclear MTOC in Drosophila fat body cells that is anchored by Msp300/Nesprin at the cytoplasmic surface of the nucleus. Msp300 recruits the MT minus-end protein Patronin/CAMSAP, which functions redundantly with Ninein to further recr… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 92 publications
(107 reference statements)
0
1
0
Order By: Relevance
“…These proteins bind directly to a/b-tubulin dimers and can either catalyse their assembly into microtubule polymers or stabilise nascent microtubule polymers. The extent to which γ-TuRC-independent nucleation occurs within cells remains unclear, but examples of γ-TuRC independent nucleation occurring both naturally (Coquand et al, 2021;Nashchekin et al, 2016;Tanaka et al, 2012;Wang et al, 2015;Zheng et al, 2019) and after γ-TuRC depletion (Hannak et al, 2002;Llamazares et al, 1999;Sampaio et al, 2001;Tsuchiya and Goshima, 2021) have been reported.…”
Section: Introductionmentioning
confidence: 99%
“…These proteins bind directly to a/b-tubulin dimers and can either catalyse their assembly into microtubule polymers or stabilise nascent microtubule polymers. The extent to which γ-TuRC-independent nucleation occurs within cells remains unclear, but examples of γ-TuRC independent nucleation occurring both naturally (Coquand et al, 2021;Nashchekin et al, 2016;Tanaka et al, 2012;Wang et al, 2015;Zheng et al, 2019) and after γ-TuRC depletion (Hannak et al, 2002;Llamazares et al, 1999;Sampaio et al, 2001;Tsuchiya and Goshima, 2021) have been reported.…”
Section: Introductionmentioning
confidence: 99%